The application of negative pressure wound therapy in orthopedics: current concepts - Landi, Giovanni; Mottola, Luciano; Braile, Adriano; Pezzella, Raffaele; De Cicco, Annalisa; Conza, Gianluca; Toro, Giuseppe; Schiavone Panni, Alfredo (Lo Scalpello - Journal, 2022)
We conducted a literature review to better understand the correct application and indications of negative pressure wound therapy (NPWT) in orthopedics and traumatology. A literature search was conducted on PubMed and all articles in English, Spanish, and Italian were included. Relevant articles, references, data, and relevant findings were identified, reviewed, extracted, and accepted by consensus of at least 66% of the researchers. Relevant articles were discussed by the research group. NPWT has several beneficial effects on the wound that contribute to the maintenance of a favorable biochemical and cellular environment, to the formation of granulation tissue and to faster healing. NWPT can be useful in the treatment of septic wounds after initial debridement surgery and removal of the septic foci, and in necrotizing fasciitis in the presence of gas gangrene, venous or pressure ulcers. NPWT can also be used “for prophylactic purposes” (incisional NPWT) in patients with risk factors for skin dehiscence and with a high risk of wound drainage in the post-operative period and after prosthetic surgery or internal fixation to protect the surgical scar. However, the available evidence is mostly unclear. The appropriate use of NPWT seems to reduce the number of dressing changes in complex wounds, reduce hospitalization times, and offer greater comfort to the patient; when applied on surgical incisions, it may reduce the risk of delayed healing and the risk of infections.